Understanding the knowledge, attitudes, and practices of stakeholders in reporting African swine fever cases in Abuyog, Leyte, Philippines. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to assess the knowledge, attitudes, and practices (KAP) of key stakeholders regarding African swine fever (ASF) and its reporting in Abuyog, Leyte, Philippines. It also aimed to identify sociodemographic factors associated with KAP levels. Materials and Methods: A cross-sectional survey was performed on 392 respondents, including pig farmers (n = 333), butchers (n = 38), live pig/meat sellers (n = 11), and Local Government Unit personnel (n = 10) between November 2023 and February 2024. KAP scores were calculated and categorized into “poor” and “good” using a median cutoff. Logistic regression analyses were conducted to investigate the association between sociodemographic variables and KAP levels. Results: Most participants showed poor knowledge of ASF causative agents, transmission, and clinical signs (83.93%) and disease recognition (60.20%), but many have good knowledge of ASF reporting protocols (70.92%). Attending ASF seminars/training was associated with improved basic ASF knowledge, disease recognition, and case reporting. Basic knowledge of ASF could enhance disease recognition. Disease recognition could then enhance ASF case reporting. Younger stakeholders showed better knowledge of basic ASF concepts. Pig farmers exhibited poor knowledge of disease recognition. Most participants showed good attitudes toward ASF reporting (97.7%), which was associated with overall knowledge of ASF. Most participants showed good practices in the early steps of case reporting (85.20%), relatively balanced on reporting protocol (49.23%), and relatively poor knowledge-seeking behavior (45.41%). Pig farmers were less likely to report than other stakeholders. Good overall knowledge translates into good practices. Overall practices are influenced by the primary source of income. Conclusion: The findings reveal a notable gap in knowledge concerning ASF among participants, highlighting an essential need for enhanced educational initiatives. Strengthening basic ASF knowledge is vital, as it positively impacts disease recognition and, in turn, case reporting. Although there is a generally positive attitude toward ASF reporting, the lack of knowledge-seeking behavior and the variability in reporting practices based on income sources suggest a need for tailored educational programs.J. Adv. Vet. Anim. Res., 12(2): 629–646, June 2025http://doi.org/10.5455/javar.2025.l927